Technological And Chemical Properties Of Chestnut (Castanea Sativa Mill.) Wood After Heat Treatment - Ateş, Saim; Akyıldız, Mehmet Hakan; Özdemir, Hasan; Gümüşkaya, Esat (Romanian Biotechnological Letters Vol. 15, No.1,4949-4958 (2010, 2010)
This study was performed to determine the effects of heat treatment on air-dry density (Dm), oven-dry density (D0), shrinkage (β), swelling (α), fiber saturation point (FSP), compression strength parallel to grain (σc//), bending strength (σb), modulus of elasticity (MOE) in bending, brinell-hardness (HB), equilibrium moisture content (EMC), chemical content and cellulose crystallinity of chestnut (Castanea sativa Mill.) wood. Wood samples were treated to heat at three different temperature (130, 180 and 230oC) and two different time level (2 and 8 h) under atmospheric pressure and presence of air. Dm, D0, β, α, FSP, EMC, σc//, σb and MOE were decreased by heat treatment. Lignin content, 1% NaOH and alcohol solubility values increased with depend on the heating temperature and time. Cellulose crystallinity of the samples was not changed significantly. Consequently, for heat treatment process, 130oC for 2 h should be applied in place where mechanical properties are important. However, 230oC for 2 h should be used in place where preferred physical properties. Heat-treated chestnut woods could be utilized by using proper heat treatment techniques in outdoors and indoors applications for several purposes such as musical instruments, kitchen furniture, garden furniture and windows frames
Keywords: Chestnut, Heat treatment, Physical properties, Mechanical properties, Chemical properties, FT-IR